2012
DOI: 10.17305/bjbms.2012.2480
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA 4977 bp deletion is a common phenomenon in hair and increases with age

Abstract: Mitochondrial DNA (mtDNA) is believed to be particularly susceptible to oxidative damage during aging, resulting in mtDNA point mutations, duplications, and deletions. Although mtDNA deletions have been reported in various human tissues, e.g., the brain, heart, and skeletal muscle, little is known about the occurrence in hair. Therefore, we screened for the presence of mtDNA 13162 bp, 10422 bp, 7663 bp, 7436 bp, 4989 bp, and 4977 bp deletions in 90 hair samples from subjects aged 5 days to 91 years by using po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…It was identified that the incidence of mtDNA CD4977 in patients with presbycusis was significantly higher as compared with the age-matched normal hearing control individuals (67.82% vs. 8.42%, P=0.000). The presented PCR results are consistent with a previous study (7). Furthermore, the PCR products indicated the absence of mtDNA CD4977 in positive individuals verified by nested-PCR amplication (Fig.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…It was identified that the incidence of mtDNA CD4977 in patients with presbycusis was significantly higher as compared with the age-matched normal hearing control individuals (67.82% vs. 8.42%, P=0.000). The presented PCR results are consistent with a previous study (7). Furthermore, the PCR products indicated the absence of mtDNA CD4977 in positive individuals verified by nested-PCR amplication (Fig.…”
supporting
confidence: 92%
“…Cochlea tissue is rich in mtDNA, which have a high probability of deletion. The deletions in mtDNA in cochlea tissue have been shown to include mtDNA 13162, 10422, 7663, 7436, 4989 and 4977 bp deletions, with the mtDNA CD4977 being the most common in cochlea tissue (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the relative proportion of mtDNA carrying the “common deletion” is known to be associated with increasing age and mortality [34, 35], we performed fixed-effect regression analysis to determine the association of both measurements of mtDNA copy number and mitochondrial injury with age. After correcting for the subset with measurements from both BA7 and BA8, we found that there was no association between the levels of mtDNA per cell and age (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial damage, particularly as a result of oxidative influences, can contribute to changes, such as deletions or mutations, in mitochondrial DNA. Analysis of hair fibers from participants ranging in age from 5 days to 91 years has revealed an increase in the incidence of a specific mitochondrial deletion over time, with 4,977 base-pair deletions by year 91 [32]. This rise in the frequency of base-pair deletions theoretically corresponds to a longer exposure to damaging effects like those from oxidation.…”
Section: Contributors To Hair Agingmentioning
confidence: 99%